PENGEMBANGAN BAHAN AJAR BERBASIS CERITA BERGAMBAR UNTUK MENINGKAT PEMAHAMAN BELAJAR BAHASA INDONESIA PADA KELAS II DI SD NEGERI 95 PALEMBANG - Yuyun Desti; Liza Murniviyanti; Aldora Pratama (PT. Jurnal Center Indonesia Publisher, 2025)
The development of illustrated story-based teaching materials to improve understanding of learning Indonesian in class II, has the goal of knowing the development of understanding of learning Indonesian that is valid, practical and effective. The type of research used by researchers in developing teaching materials based on picture stories is research and development, development refers to the ADDIE model consisting of analysis design, development, implementation, and evaluation. The research subjects were class IIA and IIB students of Public Elementary School 95 Palembang with a total of 36 students. The data collection techniques used in the study were questionnaires and documentation, based on the results of expert validator research from the three fields, namely media, material, and language where the validator in In this development, there are 2 validators covering the three fields, so the validator percentage results from the two experts are 3.80 which are categorized as